Escherichia coli proteins uL29 and ACP stabilize the Tn7-encoded TnsD and its DNA binding - Shani B. Leyva Camacho; Lindsay A. Matthews; Alba Guarné (Mobile DNA)
Abstract Tn7 mobile genetic elements are known for their sophisticated target-site selection mechanisms and, in some cases, programmability. Recognition of target sites is mediated by designated transposon-encoded proteins and modulated by host factor proteins. In the case of the CRISPR-associated Tn7 elements from the type V-K, the ribosomal protein uS15 is an integral component of recruitment complex that promotes R-loop completion. Previous biochemical work also revealed that the ribosomal protein uL29 and the acyl carrier protein (ACP) influence Tn7 transposition frequency in vitro. However, how uL29 and ACP regulate the formation of the Tn7 targeting complex remains unclear. The prototypical Tn7 element encodes a heteromeric transposase (TnsA, TnsB), a AAA + adaptor (TnsC), and two target-site selection proteins (TnsD and TnsE). TnsD targets a highly conserved site at the end of the glmS gene (attTn7). However, poor protein stability has precluded the molecular characterization of how TnsD recognizes its target site. Here, we show that ACP and uL29 interact with the C-terminal region of TnsD through reciprocal electrostatic interactions, in turn, mitigating its tendency to aggregate. Additionally, we identify the uL29 and ACP residues that mediate the interaction with TnsD and stimulate DNA binding. These results unveil unique features of the TnsD-mediated target-site selection complex.